Depolarizing effect of neocortical chandelier neurons - Woodruff, Alan; Xu, Qing; Anderson, Stewart A.; Yuste, Rafael (Frontiers in Neural Circuits, 2009)
Chandelier (or axo-axonic) cells are one of the most distinctive types of GABAergic interneurons in the cortex. Although they have traditionally been considered inhibitory neurons, data from rat and human neocortical preparations suggest that chandelier cells have a depolarizing effect on pyramidal neurons at resting membrane potential, and could even activate synaptic chains of neurons. At the same time, recent results from rat hippocampal chandeliers indicate a predominantly inhibitory effect on their postsynaptic targets. To better understand the function of chandelier neurons, we generated Nkx2.1Cre MADM mice, a strain of genetically engineered animals that, by expressing GFP in a subset of neocortical interneurons, enable the identification and targeting of chandelier cells in living brain slices. Using these mice, we characterized the basic electrophysiological properties of a homogeneous population of chandelier neurons from upper layers of somatosensory cortical slices. These chandelier cells have characteristic axon cartridges and stereotypical electrophysiological features, distinguishable from basket cells. To investigate the effect of chandelier cells on target neurons, we performed paired recordings from chandeliers and postsynaptic pyramidal cells. In both perforated patch and cell-attached configurations, chandelier PSPs consistently have a reversal potential that is depolarized from rest. Our results support the idea that chandelier cells depolarize pyramidal neurons and could potentially have an excitatory effect on the network at rest.